Geneza i rozwój szkolnego ustawodawstwa Kościoła w epoce średniowiecza (rekonesans) - Ratajczak, Krzysztof (Biuletyn Historii Wychowania, 2014)
The aim of the article is to present the beginnings and the subsequent development and evolution of church law in the sphere of education from the 4th to the beginning of the 16th century. The roots of the acts of law presented by the Popes, synods and councils were based on the traditions of Roman law, but a variety of reasons from the field of policy, economy and society led to the need to establish a church school system. The aim of the Church was to create an independent school system with its own purposes, different from civil schools. The article shows the main factors in the development of the legislation in the sphere of education and the functioning of the schools, and the relationship between civil and Church leaders. Another field of analysis is to search for the inspirations, aims and reception of the law in cathedral, collegiate, parish and monastic schools.